Flujo de potencia AC descentralizado para sistemas de potencia multi-área usando un método de descomposición basado en relajación Lagrangiana - Echeverri, Mauricio Granada; Lezama, Jesús María López; Mantovani, José Roberto Sánchez [UNESP] (My University, 2010)
A decentralized solution method to the AC power flow problem in power systems with interconnected areas is presented. The proposed methodology allows finding the operation point of a particular area without explicit knowledge of network data of adjacent areas, being only necessary to exchange border information related to the interconnection lines between areas. The methodology is based on the decomposition of the first-order optimality conditions of the AC power flow, which is formulated as a nonlinear programming problem. A 9-bus didactic system, the IEEE Three Area RTS-96 and the IEEE 118 bus test systems are used in order to show the operation and effectiveness of the distributed AC power flow.
Decentralized AC power flow for multi-area power systems using a decomposition approach based on Lagrangian relaxation
Keywords: Decentralized power flow; Decomposition techniques; Multi-area power systems